Comparative studies of the influence of particle size on various pretreatments of rice husk by assessment of chemical and structural components and wastewater characteristics of liquid fraction - Shahabazuddin, Mohmmad; Banuvalli, Bhavana Karibasappa; Mulik, Nagesh; Pande, Ashwini; Bokade, Vijay; Mudliar, Sandeep Narayan (Biomass Conversion and Biorefinery, 2023)
The dilute acid (DA), steam explosion (SE), and a 2-step: steam explosion followed by alkali (SEA) were evaluated for pretreatment of rice husk. The maximum hemicellulose and lignin removal via degradation and dissolution was observed for SEA pretreatment, enabling higher cellulose enrichment (up to 44% w/w) and recovery (up to 78%). The hemicellulose solubilization was >90% for all the pretreatments, while maximum lignin removal (up to 62%) was observed for SEA pretreatment. The particle size in the range of 0.3-0.6 mm enabled higher pretreatment efficiencies in terms of cellulose enrichment. The liquid fraction obtained after DA pretreatment indicated higher COD values (20800-24440 mg/L) as compared to SEA (7800-11400 mg/L) due to lower cellulose recoveries in DAP (54-68%). SEM analysis of the biomass indicated disrupted regions with multiple pores. FTIR analysis revealed cleavage of lignin side chains, and XRD analysis confirmed the increase in cellulose crystallinity post-pretreatment.
Keywords: Lignocellulosic crop residues; Liquid-waste characterization; Particle size; Rice husk biomass; Steam explosion pretreatment

Continuous flow β-zeolite catalysed regioselective alkylation of naphthols using alcohols for synthesis of peroxynaphthalen-2(1H)-one, Azidonaphthalen-2(1H)-one and Fluoronaphthalen-2(1H)-one derivatives - Londhe, Gokul; Bokade, Vijay; Gnanaprakasam, Boopathy (Asian Journal of Organic Chemistry, 2025)
Functionalized naphthols are prominent scaffolds in organic synthesis and materials chemistry. Herein, we demonstrated continuous flow alkylation of alpha- and beta-naphthols by using various primary and secondary benzylic alcohols in the presence of environmentally benign granular beta-zeolite as a reusable catalyst. For a variety of beta-naphthols, the respective alkylated products with good regioselectivity were obtained in high yields under mild reaction conditions. This protocol proceeded via the classical Friedel-Crafts type alkylation process and generated stable carbocations as intermediates. Applying this protocol, versatile naphthol derivatives have been synthesized using primary and secondary benzylic alcohols (50 and 44 examples in batch and continuous flow process, respectively), with good yields. Key advantages of this process includes rapid and efficient transformation, facilitates gram-scale synthesis, and generates water as the sole by-product. The most significant advantage is the continuous reusability of granular beta-zeolite, which further emphasizes the sustainability of the method. The application of alkylated naphthols for quaternary functionalization was demonstrated through peroxidation, azidation, and halogenation reactions under the continuous flow module, which yielded the respective peroxynaphthalen-2(1H)-one, azidonaphthalen-2(1H)-one and fluoronaphthalen2(1H)-one derivatives.
Keywords: continuous flow; Multigram Synthesis; Reusable beta-zeolite; Sustainable Appraoch; Transition metal free